A cellulose chitosan composite UiO-66-NH2 microsphere and its preparation method and application

By growing UiO-66-NH2 in situ on cellulose chitosan microspheres, using its pores and cellulose chitosan functional groups, the problem of basic dye wastewater treatment is solved, and efficient adsorption and removal is achieved. Safe and environmentally friendly.

CN116212827BActive Publication Date: 2025-02-14HUBEI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310349153.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-02-14
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat alkaline dye wastewater, resulting in environmental pollution and ecological damage.

Method used

By selecting chitosan and cellulose as raw materials, UiO-66-NH2 grows in situ on cellulose chitosan microspheres, using the effects of raw material functional groups and dye molecules, and the pores of UiO-66-NH2 material to alkaline Dyes are adsorbed.

Benefits of technology

It significantly improves the adsorption performance, achieves efficient removal of alkaline dyes, and the material is non-toxic and pollution-free, and has wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212827B_ABST
    Figure CN116212827B_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose chitosan composite UiO‑66‑NH2 microsphere and a preparation method and application thereof. The preparation method of the cellulose chitosan composite UiO‑66‑NH2 microsphere comprises the following steps: adding chitosan and cellulose to an organic solution to form a viscous solution; adding the viscous solution to an ethanol aqueous solution of sodium hydroxide to form transparent microspheres; washing to neutrality, drying to obtain cellulose chitosan composite microspheres; ZrCl4 and 2‑aminoterephthalic acid are dissolved in DMF, stirred and dissolved to obtain a reaction solution; the reaction solution and the cellulose chitosan composite microspheres are moved to a reactor for reaction, filtered or centrifuged to obtain microspheres, and dried. The present invention utilizes the intermolecular forces between the amino and carboxyl functional groups of cellulose chitosan and dye molecules, and the inherent pores of UiO‑66‑NH2 to adsorb the dye, and the preparation is simple, the material is non-toxic and pollution-free, and has a wide range of application prospects and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of basic dye adsorption materials, and in particular relates to a cellulose chitosan composite UiO-66-NH2 microsphere and a preparation method and application thereof. Background Art

[0002] At present, the usual method for pre-treatment of printing and dyeing wastewater is physical method, followed by chemical treatment to achieve the comprehensive treatment goal. The main physical pre-treatment methods include flocculation, acid neutralization adsorption, membrane separation technology, etc. Among them, adsorption method is particularly suitable for colored wastewater that is difficult to chemically treat, such as activated carbon adsorption, but it can only be used to treat water-soluble dyes, and suspended solids and water-insoluble dyes cannot be treated.

[0003] Cellulose and chitosan are the most abundant natural polymers in the world that are renewable and easily degradable. Cellulose also has abundant hydroxyl and carboxyl groups, and has good water solubility and hydrophilicity. At present, there have been reports on the use of chitosan as a flocculant for wastewater treatment. The molecular structure of chitosan contains a large number of free amino and hydroxyl groups, which are flat bond structures from the perspective of the three-dimensional structure, so that it has a chelating effect on some ions with a certain ionic radius, and can fully utilize the intermolecular forces between functional groups for adsorption, thereby increasing the adsorption effect. In addition, chitosan also has the green characteristics of being easy to degrade, environmentally friendly, and non-toxic. Metal-organic framework materials (MOFs) are porous coordination polymers formed by the self-assembly of metal ions and organic complexes. It has the properties of large porosity, large specific surface area, and luminescence, and has many applications in the fields of gas storage and adsorption. Common MOFs materials mainly include UiO family, IRMOF family, ZIF family, etc. Among them, MOFs of the UiO family are based on Zr 4+ As the metal ion center, Zr 4+ It is oxygen-philic and therefore stable in various solvents. The more common UiO family MOFs include UiO-66, UiO-67, and modified UiO-66-NH2, UiO-66-NO2, etc. The modified MOFs material not only does not change its three-dimensional structure, but also increases its reaction sites, thereby expanding the application field of MOFs materials.

[0004] There are many treatment methods for acidic printing and dyeing wastewater. However, there are not many treatment methods for alkaline dyes, which belong to industrial wastewater. If they are discharged directly without treatment, they will corrode pipes, canals and buildings, change the pH value of water bodies, damage the ecological environment of rivers, and destroy water resources. Therefore, there is an urgent need to prepare biosorbents for treating alkaline dyes. Summary of the invention

[0005] In view of the defects of the prior art, a cellulose chitosan composite UiO-66-NH2 microsphere and its preparation method and application are provided. The present invention selects chitosan and cellulose as raw materials, selects UiO-66-NH2 to grow in situ on the cellulose chitosan microsphere, and utilizes the intermolecular forces between the amino and carboxyl functional groups of the raw material cellulose chitosan and the dye molecules, and the inherent pores of UiO-66-NH2 to adsorb the dye. The adsorption performance of the composite microsphere is significantly enhanced from the microstructure, and the preparation method is simple, the material is non-toxic and pollution-free, and it has broad application prospects and application value.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing cellulose chitosan composite UiO-66-NH2 microspheres comprises the following steps:

[0008] (1) adding chitosan and cellulose to an organic solution and stirring to form a viscous solution;

[0009] (2) adding the viscous solution described in step (1) to an ethanol aqueous solution of sodium hydroxide to form transparent microspheres;

[0010] (3) washing the transparent microspheres in step (2) until they are neutral, and then drying to obtain cellulose chitosan composite microspheres;

[0011] (4) ZrCl4 and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide and stirred at room temperature until fully dissolved to obtain a reaction solution; the reaction solution and the cellulose chitosan composite microspheres described in step (3) are transferred to a reaction kettle, reacted at 100-120° C. for 12-24 h, and after the reaction is completed, the microspheres are filtered or centrifuged to obtain the microspheres, and finally dried to prepare the cellulose chitosan composite UiO-66-NH2 microspheres.

[0012] Preferably, the organic solution in step (1) is an acetic acid solution.

[0013] Preferably, the solubility of the acetic acid solution is 1 to 3% (v / v).

[0014] Preferably, in step (1), the mass ratio of cellulose to chitosan is 1:0.5-2.

[0015] Preferably, in step (1), the stirring is performed at 25 to 40° C. for 4 to 12 hours.

[0016] Preferably, in step (1), the mass volume ratio of chitosan to organic solvent is 0.01 to 0.03 g / mL.

[0017] Preferably, in step (2), the sodium hydroxide concentration of the ethanol aqueous solution of sodium hydroxide is 1 to 3 mol / L.

[0018] Preferably, in step (2), the mass of ethanol in the ethanol aqueous solution of sodium hydroxide accounts for 40 to 60 wt % of the total amount.

[0019] Preferably, in step (3), washing is performed by washing with water and ethanol in sequence.

[0020] Preferably, in step (3), the drying temperature is 25 to 40° C. and the drying time is 5 to 12 hours.

[0021] Preferably, in step (4), the molar ratio of ZrCl4 and 2-aminoterephthalic acid added is 1:1-2.

[0022] Preferably, in step (4), the mass ratio of ZrCl4 to the chitosan described in step (1) is 1:5-10.

[0023] Preferably, in step (4), the drying temperature is 25 to 60° C., and the drying time is 10 to 24 hours.

[0024] The cellulose chitosan composite UiO-66-NH2 microspheres prepared by the above-mentioned preparation method of cellulose chitosan composite UiO-66-NH2 microspheres.

[0025] The above-mentioned cellulose chitosan composite UiO-66-NH2 microspheres are used as alkaline dye adsorbents.

[0026] Preferably, the application includes the following steps: adding cellulose chitosan composite UiO-66-NH2 microspheres into alkaline dye wastewater at a ratio of 0.9-1.1 g:1 L, stirring to make the cellulose chitosan composite UiO-66-NH2 microspheres evenly dispersed in the wastewater, and leaving it for 10-24 hours to complete the adsorption of the alkaline dye.

[0027] Preferably, the concentration of the basic dye is 5 to 20 mg / L.

[0028] Preferably, the basic dye is at least one of methylene blue and crystal violet.

[0029] The specific mechanism of action of the cellulose chitosan composite UiO-66-NH2 microspheres for adsorbing dyes is as follows:

[0030] Physical adsorption of cellulose chitosan UiO-66-NH2 materials: Physical adsorption is related to specific surface area. The larger the specific surface area, the greater the surface energy, the greater the surface tension, and the better the adsorption performance. Compared with previous adsorption materials, the cellulose chitosan UiO-66-NH2 composite microspheres prepared in Example 1 of the present invention have a microsphere morphology that increases the specific surface area of ​​the adsorbent and the contact area with the dye, thereby improving the adsorption removal rate; at the same time, the inherent pores of the UiO-66-NH2 material grown in situ on the surface of the microspheres can capture dye molecules, thereby improving the adsorption rate of the dye.

[0031] Chemical adsorption of cellulose chitosan UiO-66-NH2 materials: Hydrogen bonding: Cellulose and chitosan molecules as adsorbent molecules contain a large number of free amino groups and hydroxyl groups. UiO-66-NH2 also contains a large number of free amino groups, which interact with the nitrogen cations in the alkaline dye molecules through hydrogen bonding and are adsorbed by the adsorbent; Covalent bonding: Since the amino groups and hydroxyl groups on the surfaces of cellulose, chitosan and UiO-66-NH2 in the adsorbent are ionized in water to form pro-ions, they are in an unsaturated state and exhibit negative charge in aqueous solution. Therefore, they can form covalent chemical bonds with positively charged dye molecules through electron acceptance and sharing, thereby combining the dye molecules with the adsorbent. The strength of the adsorbent's adsorption capacity depends on whether it can effectively receive or supply electrons. If the chemical structure of the dye molecule has similar electronic properties to the adsorbent, the adsorption will be more firm.

[0032] Compared with the prior art, the beneficial effects of the present invention include:

[0033] (1) Cellulose chitosan microspheres are used to adsorb dyes. A Chinese invention patent (CN113457736A) discloses a preparation method and application of chitosan / cellulose immobilized copper composite microspheres. This patent uses composite copper microspheres to catalyze the boron addition reaction of α,β-unsaturated compounds. The present invention improves the original chitosan / cellulose microspheres, grows UiO-66-NH2 in situ on the chitosan / cellulose composite microspheres, and uses the free amino and hydroxyl groups of the raw materials cellulose and chitosan and the pores of the UiO-66-NH2 material to adsorb alkaline materials.

[0034] (2) The addition of UiO-66-NH2 material improves adsorption stability. Although simple cellulose chitosan composite microspheres contain free hydroxyl groups and amino groups, it is far from enough to adsorb dye molecules only through weak intermolecular forces such as hydrogen bonding forces, and the removal rate is almost 0. The present invention grows UiO-66-NH2 in situ on chitosan / cellulose composite microspheres, and introduces UiO-66-NH2 material with pores into the original material. While the cellulose chitosan molecules adsorb the dye molecules, the UiO-66-NH2 material is used to fix the dye molecules, thereby improving the adsorption stability of the adsorption material.

[0035] (3) Selection of UiO materials. Considering that amino groups are the functional groups of chitosan for dye adsorption, the use of functionalized UiO-66-NH2 to modify the cellulose chitosan composite microspheres can increase the number of free amino groups in the adsorbent material and provide more reaction sites. The adsorbent is adsorbed by the adsorbent through hydrogen bond interactions with the nitrogen cations in the alkaline dye molecules; since the amino and hydroxyl groups on the surfaces of cellulose, chitosan and UiO-66-NH2 in the adsorbent are in an unsaturated state and exhibit negative charge in aqueous solution, they can form chemical bonds or generate surface complexes with positively charged dye molecules through electron acceptance and sharing, thereby binding the dye molecules to the adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a photo of the cellulose chitosan UiO-66-NH2 composite microspheres prepared in Example 1 of the present invention.

[0037] Figure 2 This is a comparison chart of infrared spectra of the cellulose chitosan composite microspheres, chitosan and cellulose prepared in step (3) of Example 1 of the present invention.

[0038] Figure 3 This is a comparison chart of infrared spectra of the cellulose chitosan UiO-66-NH2 composite microspheres and UiO-66-NH2 microspheres prepared in step (4) of Example 1 of the present invention.

[0039] Figure 4 This is a comparison chart of the removal rates of various dyes by the cellulose chitosan composite microspheres prepared in Example 1 of the present invention over time.

[0040] Figure 5 This is a comparison chart of the removal rates of various dyes by the cellulose chitosan UiO-66-NH2 composite microspheres prepared in Example 1 of the present invention over time.

[0041] Figure 6 This is a scanning electron microscope image of the cellulose chitosan composite microspheres prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] The cellulose used in the examples was purchased from Aladdin Company and was named microcrystalline cellulose.

[0044] Example 1

[0045] A method for preparing cellulose chitosan composite UiO-66-NH2 microspheres, the steps are as follows:

[0046] (1) Add 500 mg of cellulose particles and 1.0 g of chitosan (0.006 mol) to 100 ml of distilled water containing 2.0 ml of acetic acid, and stir to obtain a viscous liquid. The hydroxyl group and amino group in the chitosan molecule are both active groups, which can adsorb dye ions through coordination, ion exchange and electrostatic action, but the strength and acid resistance of chitosan are poor. Cellulose has high tensile strength, is similar to the molecular structure of chitosan, and is compatible. Therefore, the present invention improves the material strength by blending cellulose and chitosan, and at the same time improves the pore structure and surface characteristics of the adsorbent, which is beneficial to improving the adsorption performance;

[0047] (2) The obtained viscous liquid is slowly dripped into 100 mL of sodium hydroxide ethanol aqueous solution (prepared by 12 g of sodium hydroxide, 40 mL of distilled water, and 60 mL of ethanol) with a syringe to form transparent microspheres. Sodium hydroxide solution is a poor solvent for cellulose and chitosan. After the chitosan cellulose solution is dripped into the sodium hydroxide solution, it remains spherical due to its insolubility. The dripping process is as high and far as possible; in this step, ethanol is used to cause pores on the surface of the microspheres to improve the adsorption effect;

[0048] (3) filtering the obtained microspheres, washing them with distilled water and ethanol until they are neutral; placing the washed microspheres in a watch glass, and drying them in an oven at 30° C. for 12 h to prepare cellulose chitosan composite microspheres;

[0049] (4) Dissolve 0.233 g ZrCl4 and 0.181 g 2-aminoterephthalic acid in DMF and stir at room temperature until fully dissolved; transfer the dissolved solution and the cellulose chitosan microspheres obtained in step (3) to a reactor, place them in an oven at 120°C and heat them for 24 h. After natural cooling, filter out the microspheres, rinse them with DMF and anhydrous ethanol three times each, and place the obtained microspheres in an oven at 60°C and dry them for 10 h to finally obtain cellulose chitosan UiO-66-NH2 composite microspheres.

[0050] Example 2

[0051] A method for preparing cellulose chitosan composite microspheres, comprising the following steps:

[0052] (1) Add 500 mg of cellulose particles to 100 ml of chitosan solution (100 ml of water, 500 mg of chitosan, 2.0 ml of acetic acid) and stir until uniform to obtain a viscous solution.

[0053] (2) The prepared viscous liquid is slowly dripped into 100 mL of sodium hydroxide ethanol aqueous solution (prepared by 12 g of sodium hydroxide, 40 mL of distilled water, and 60 mL of ethanol) with a syringe to form transparent microspheres; sodium hydroxide solution is a poor solvent for cellulose and chitosan. After the chitosan cellulose solution is dripped into the sodium hydroxide solution, it remains spherical due to its insolubility. The dripping process is as high and far as possible. In this step, ethanol is used to cause pores;

[0054] (3) Filtering the obtained microspheres, washing with distilled water and ethanol until neutral; placing the washed microspheres in a watch glass, and baking in an oven at 30° C. for 12 h, thereby finally preparing cellulose chitosan composite microspheres.

[0055] Example 3

[0056] The cellulose chitosan UiO-66-NH2 composite microspheres and cellulose chitosan composite microspheres prepared in Examples 1 and 2 were added to the methylene blue wastewater with a concentration of 5 mg / L according to a ratio of 0.9 g: 1 L, respectively. After the adsorbent was uniformly dispersed in the methylene blue wastewater by mechanical stirring, the mixture was allowed to stand. The supernatant was taken for ultraviolet photometry test every 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, and the characteristic absorption peak intensity was recorded. When the characteristic absorption peak intensity of methylene blue remained unchanged, the adsorbent (cellulose chitosan UiO-66-NH2 composite microspheres or cellulose chitosan composite microspheres) adsorbed the dye to reach equilibrium. The results showed that the removal rate of methylene blue by cellulose chitosan composite microspheres was only 7%, but the removal rate of cellulose chitosan UiO-66-NH2 composite microspheres was as high as 58%.

[0057] Example 4

[0058] The "5 mg / L methylene blue waste liquid" in Example 3 was replaced by "golden orange waste liquid (concentration of 5 mg / L)", and the other steps were the same as Example 3. The results showed that the removal rates of cellulose chitosan composite microspheres and cellulose chitosan UiO-66-NH2 composite microspheres for golden orange were both less than 5%.

[0059] Example 5

[0060] The "5 mg / L methylene blue waste liquid)" in Example 3 was replaced with "lissamine rhodamine B waste liquid (concentration of 5 mg / L)", and the other steps were the same as Example 3. The results showed that the removal rates of lissamine rhodamine B by cellulose chitosan composite microspheres and cellulose chitosan UiO-66-NH2 composite microspheres were both less than 5%.

[0061] Example 6

[0062] The "5 mg / L methylene blue waste liquid" in Example 3 was replaced by "crystal violet waste liquid (concentration of 5 mg / L)", and the other steps were the same as Example 3. The results showed that the removal rate of crystal violet by cellulose chitosan composite microspheres was only 50%, but the removal rate of cellulose chitosan UiO-66-NH2 composite microspheres was as high as 64%.

[0063] Figure 1 This is a photo of the cellulose chitosan UiO-66-NH2 composite microspheres prepared in Example 1 of the present invention.

[0064] Figure 2 The infrared spectra of the cellulose chitosan composite microspheres, chitosan and cellulose prepared in step (3) of Example 1 of the present invention are compared. Figure 2 It can be seen that in the infrared spectrum of chitosan, 1388cm -1 and 1627cm -1 The characteristic peaks are the asymmetric stretching vibration peak of -COO- and the stretching vibration peak of CO. In the infrared spectrum of cellulose, the peaks at 3445 cm -1 (stretching vibration of NH and OH), 1380cm -1 The absorption peak appears at (NH deformation vibration). The 1627cm of cellulose in the infrared spectrum of cellulose chitosan composite microspheres -1 The characteristic peaks of the amide on chitosan overlapped, and the C=O peak on the carboxyl group and the NH bending vibration peak were at 1396 cm -1 The overlap indicates the presence of chitosan and cellulose in the composite microspheres.

[0065] Figure 3 This is a comparison of the infrared spectra of the cellulose chitosan UiO-66-NH2 composite microspheres and the UiO-66-NH2 microspheres prepared in step (4) of Example 1 of the present invention. Figure 3 It can be seen that: 1629cm -1 、1567cm -1 The peak at 1432 cm indicates the successful coordination of carboxyl group and Zr, indicating the successful synthesis of UiO-66-NH2. The characteristic peak of cellulose chitosan microspheres at 1432 cm appears in the infrared spectrum of cellulose chitosan UiO-66-NH2 composite microspheres. -1and 1571cm of UiO-66-NH2 -1 , indicating that cellulose chitosan UiO-66-NH2 composite microspheres were successfully synthesized.

[0066] The UiO-66-NH2 material was prepared according to the following steps: 0.233g ZrCl4 and 0.181g 2-aminoterephthalic acid were dissolved in DMF, stirred at room temperature until fully dissolved, and then transferred to a reactor, heated at 100-120°C for 20-24h, and the suspension was centrifuged after natural cooling, and washed with DMF and anhydrous ethanol for 3 times respectively. The separated product was placed in a vacuum drying oven and dried for 10h to obtain the UiO-66-NH2 material.

[0067] Figure 4 This is a comparison chart of the removal rate of various dyes by cellulose chitosan composite microspheres prepared in Example 1 of the present invention over time; Figure 5 This is a comparison chart of the removal rate of various dyes by the cellulose chitosan UiO-66-NH2 composite microspheres prepared in Example 1 of the present invention over time; combined with Figures 4-5 We can see that the cellulose chitosan composite microspheres and cellulose chitosan UiO-66-NH2 composite microspheres can selectively adsorb the basic dyes crystal violet and methylene blue, and the adsorption reaches equilibrium within 5 hours, and the adsorption is rapid. In addition, due to the addition of the UiO-66-NH2 metal organic framework, the cellulose chitosan UiO-66-NH2 composite microspheres significantly improve the adsorption of the basic dye methylene blue, and the removal rate is increased from 7% to 58%. It also improves the adsorption capacity of crystal violet dye. However, the acid dyes golden orange and lissamine rhodamine B dyes are almost not adsorbed. The possible reason is that the hydroxyl and amino groups in the cellulose chitosan UiO-66-NH2 composite microsphere material are negatively charged in aqueous solution, which has a repulsive effect on the acid dye molecules with the same negative charge, which is not conducive to the adsorption of acid dyes.

[0068] Figure 6 This is a scanning electron microscope image of the cellulose chitosan composite microspheres prepared in Example 1 of the present invention. Figure 6 It can be seen that the cellulose chitosan composite microspheres are elliptical microspheres, and tiny holes can be seen on the surface of the microspheres, which can adsorb basic dye molecules.

[0069] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. Application of cellulose chitosan composite UiO-66-NH2 microspheres as alkaline dye adsorbent, characterized in that: The concentration of the basic dye is 5-20 mg / L; The basic dye is at least one of methylene blue and crystal violet; The preparation method of the cellulose chitosan composite UiO-66-NH2 microspheres comprises the following steps: (1) Add chitosan and cellulose to an organic solution and stir to form a viscous solution; (2) adding the viscous solution of step (1) into an ethanol aqueous solution of sodium hydroxide to form transparent microspheres; (3) washing the transparent microspheres in step (2) until they are neutral, and then drying them to obtain cellulose chitosan composite microspheres; (4) ZrCl4 and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide and stirred at room temperature until fully dissolved to obtain a reaction solution; the reaction solution and the cellulose chitosan composite microspheres described in step (3) are transferred to a reaction kettle and reacted at 100-120° C. for 12-24 h. After the reaction is completed, the microspheres are filtered or centrifuged to obtain the microspheres, and finally dried to prepare the cellulose chitosan composite UiO-66-NH2 microspheres.

2. The use according to claim 1, characterized in that: The method comprises the following steps: adding cellulose chitosan composite UiO-66-NH2 microspheres into alkaline dye wastewater at a ratio of 0.9-1.1 g: 1 L, stirring to make the cellulose chitosan composite UiO-66-NH2 microspheres evenly dispersed in the wastewater, and placing the microspheres for 10-24 hours to complete the adsorption of the alkaline dye.

3. The use according to claim 1, characterized in that: The organic solution in step (1) is an acetic acid solution; The mass ratio of cellulose to chitosan in step (1) is 1:0.5-2.

4. The use according to claim 3, characterized in that: The mass volume ratio of the chitosan to the organic solution in step (1) is 0.01-0.03 g / mL; The solubility of the acetic acid solution is 1-3% (v / v).

5. The use according to claim 1, characterized in that: The sodium hydroxide concentration of the ethanol aqueous solution of sodium hydroxide in step (2) is 1-3 mol / L; In step (2), the ethanol aqueous solution of sodium hydroxide has a mass of ethanol accounting for 40-60wt% of the total mass.

6. The use according to claim 1, characterized in that: The stirring in step (1) is stirring at 25-40° C. for 4-12 hours; The drying temperature in step (3) is 25-40°C and the drying time is 5-12 hours; The washing in step (3) is performed by washing with water and ethanol in sequence.

7. The use according to claim 1, characterized in that: The drying temperature in step (4) is 25-60°C and the drying time is 10-24h; The molar ratio of ZrCl4 and 2-aminoterephthalic acid added in step (4) is 1:1-2; The mass ratio of the ZrCl4 in step (4) to the chitosan in step (1) is 1:5-10.

Citation Information

Patent Citations

  • Application of chitosan / cellulose composite microsphere immobilized copper in catalysis of silicon addition reaction of alpha, beta-unsaturated carbonyl compound

    CN113457736A

  • Precious metal ion adsorption material based on magnetic metal organic framework and preparation method

    CN113477220A